Examining recyclable items collection: insights from material recovery collection facility and community recycling centre - Mohammad Ramli, Abu Hanifah; Abd Manaf, Latifah; Mustafa, Hanania Mirza; Mohd Nasir, Ahadi; Mohd Subki, Abdul Hadi (Malaysian Institute Of Planners, 2024)
For city administrations, urban waste management is a crucial issue since it has an impact on public health and environmental sustainability. Reducing the amount of waste that is dumped in landfills and protecting the environment requires efficient recycling programs. This study aims to evaluate the collection of recyclable items from two distinct types of recycling centres, namely, Material Recovery Collection Facilities (MRCFs) and Community Recycling Centres (CRCs). Meanwhile, it also aims to evaluate the quantity of recyclable materials that are collected from two distinct types of recycling centres. This study utilised raw secondary data provided by KDEB Waste Management Sdn. Bhd. A statistical analysis was subsequently conducted to provide insights into the composition of recyclable items at each recycling facility. From the analysis, it is shown that the MRCFs have gathered 97.29% of recyclable items, leaving the CRCs with the remaining 2.71% in total. This highlights the value of a specialised and well-coordinated strategy for managing numerous types of recyclable waste, which enhances the overall sustainability and effectiveness of the recycling program. Therefore, this study recommends that data collection activities at each recycling centre continue with some improvements, as this could aid in future analysis of recycling patterns and trends.